Modern kitchens in the pampas: Home mechanization and domestic work in Argentina, 1940-1970 - Pérez, Inés (2015)
Discourses about the kitchen are a useful starting point to trace changing ways of looking at domestic work and women's ideals in different times, especially within the home mechanization process. This article explores the emergence of different kitchen models in Argentinean popular media during the second half of the twentieth century. Specifically, it observes the ways in which the kitchen was represented in women's magazines and how these representations were re-signified in the life stories of both men and women who witnessed and staged the mechanization of the home. Their appropriations of these models were not only diverse but also unequal. This text shows how experiences of housework and kitchen mechanization were marked by deep social and gender inequalities. It also shows the significance domestic work gained in the promotion of new modes of living and new standards of consumption.